Blockade of CD47‐mediated cathepsin S/protease‐activated receptor 2 signaling provides a therapeutic target for hepatocellular carcinoma. Issue 1 (29th May 2014) - Lee, Terence Kin‐Wah; Cheung, Vincent Chi‐Ho; Lu, Ping; Lau, Eunice Yuen Ting; Ma, Stephanie; Tang, Kwan Ho; Tong, Man; Lo, Jessica; Ng, Irene Oi Lin
<x xml:space="preserve">Abstract</x> Identification of therapeutic targets against tumor‐initiating cells (TICs) is a priority in the development of new therapeutic paradigms against cancer. We enriched a TIC population capable of tumor initiation and self‐renewal by serial passages of hepatospheres with chemotherapeutic agents. In chemoresistant hepatospheres, CD47 was found to be up‐regulated, when compared with differentiated progenies. CD47 is preferentially expressed in liver TICs, which contributed to tumor initiation, self‐renewal, and metastasis and significantly affected patients' clinical outcome. Knockdown of CD47 suppressed stem/progenitor cell characteristics. CD47+ hepatocellular carcinoma (HCC) cells preferentially secreted cathepsin S (CTSS), which regulates liver TICs through the CTSS/protease‐activated receptor 2 (PAR2) loop. Suppression of CD47 by morpholino approach suppressed growth of HCC in vivo and exerted a chemosensitization effect through blockade of CTSS/PAR2 signaling. Conclusion: These data suggest that CD47 may be an attractive therapeutic target for HCC therapy. (Hepatology 2014;60:179–191)